Peran Keahlian Keuangan Direksi dan Karakteristik Perusahaan Terhadap Penghindaran Pajak : Perusahaan di BEI - Kennardi Tanujaya; Jasinda Iriani (Universitas Internasional Batam, 2021)
Companies with directors' financial expertise have good knowledge of making tax savings by exploiting loopholes in tax regulations. The financial expertise of the directors and firm characteristics tested against tax avoidance is the aim of this study. The dependent variables used are tax avoidance and directors' financial expertise, profitability, leverage, company size, company age, tax loss compensation, tunneling incentives as independent variables.In 2015 - 2019 there were 668 companies listed on the IDX and those that met the criteria in the study were 373 companies. Secondary data testing was processed by panel regression. The test results state that profitability and company size have a positive effect on tax avoidance. Companies that have good performance and are already large company sizes tend not to avoid tax because the tax burden does not have a major impact on company expenses.